2015
DOI: 10.1063/1.4929470
|View full text |Cite
|
Sign up to set email alerts
|

Activation and dissociation of CO2 on the (001), (011), and (111) surfaces of mackinawite (FeS): A dispersion-corrected DFT study

Abstract: Iron sulfide minerals, including mackinawite (FeS), are relevant in origin of life theories, due to their potential catalytic activity towards the reduction and conversion of carbon dioxide (CO 2 ) to organic molecules, which may be applicable to the production of liquid fuels and commodity chemicals. However, the fundamental understanding of CO 2 adsorption, activation, and dissociation on FeS surfaces remains incomplete. Here, we have used density functional theory calculations, corrected for long-range disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 67 publications
4
52
0
Order By: Relevance
“…12,13 In the current search for new catalysts, transition metal sulfides have gained attention as a promising alternative, due to their high abundance, low cost, and prominent catalytic features. For example, iron sulfides have been suggested as catalysts for the activation and conversion of CO 2 , 14,15 thereby also supporting the iron-sulfur hypothesis for the origin of life by Wächtershäuser and co-workers, which proposes that many of the prebiotic chemical reactions may have been catalysed by (Ni,Fe) sulfide minerals. 16,17 Previous studies have revealed that Ni is vital to modulate an adequate redox potential in (Ni,Fe) complexes, e.g.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…12,13 In the current search for new catalysts, transition metal sulfides have gained attention as a promising alternative, due to their high abundance, low cost, and prominent catalytic features. For example, iron sulfides have been suggested as catalysts for the activation and conversion of CO 2 , 14,15 thereby also supporting the iron-sulfur hypothesis for the origin of life by Wächtershäuser and co-workers, which proposes that many of the prebiotic chemical reactions may have been catalysed by (Ni,Fe) sulfide minerals. 16,17 Previous studies have revealed that Ni is vital to modulate an adequate redox potential in (Ni,Fe) complexes, e.g.…”
Section: Introductionmentioning
confidence: 58%
“…using the Perdew-Wang 91 (PW91) 25,26 and the Perdew-Burke-Ernzerhof (PBE) 27,28 exchange-correlation functionals and taking into account spin polarization. The PW91 calculations were corrected with the spin interpolation formula of Vosko et al 29 To remain consistent with previous reports, 9,14,15 long-range dispersion interactions were added to all the simulations via the D2 30 and the zero-damping D3 (zero) 31 semi-empirical methods. Note that different vdW schemes show the same trends albeit with some differences in the absolute values.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Similar abiotic reactions have been proposed to take place on Fe(Ni)S surfaces, via Fischer–Tropsch‐type hydrogenations and Koch‐type carbonyl transfers , as shown in Figure . This reaction mechanism also depicts the first difficult step, the reduction of CO 2 to CO on an iron‐sulphide surface , which we discuss later in relation to pH modulation of reduction potential.…”
Section: The Acetyl Coa Pathway Is Ancientmentioning
confidence: 90%
“…Moreover, when possible, CO 2 adsorption normally goes without significant activation, a process that is known to require charge transfer from the substrate resulting in a concomitant bending. 14 The possible capture/activation of CO 2 has been theoretically tackled via first principles calculations on metals, [15][16][17] metal oxides, 18,19 graphene-based materials, 20 sulfides, 21 zeolites, 22 and metal-organic frameworks, 23 to name a few.…”
mentioning
confidence: 99%